Recent Progress in Adsorptive Removal of Water Pollutants by Metal‐Organic Frameworks. Issue 2 (15th December 2021) - Beydaghdari, Mohammadreza; Saboor, Fahimeh Hooriabad; Babapoor, Aziz; Asgari, Mehrdad
Abstract: Difficulty in accessing drinkable water resources, mostly originating from water pollution, has become a serious challenge for humans and the environment. Increasing population, growth of industrial activities, and the increasing demand for the agricultural sector have generated various pollutants into the environment, especially water resources. Thus, treatment of industrial effluents before discharging them into the environment is necessary to reduce the pollutants, maintain the quality of drinkable water, recycle wastewater sources to save water consumption, and minimize water resource supplied. Among the new materials applied for the adsorptive removal of pollutants from aquatic environments, metal‐organic frameworks have become a promising candidate to optimize wastewater treatment process. This is mainly due to their unique properties such as structural diversity, high specific surface area, and high adsorption capacity. This article aims to review the highlights and challenges of MOFs when are being used to remove heavy metals, dyes, pharmaceuticals, personal care products, pesticides, and herbicides from polluted water resources. The relationship between the properties of MOFs and their performance for adsorption of pollutants as well as the key mechanisms of adsorbing water pollutants using MOFs are presented. The use of water‐stable MOFs such as MOF‐235, MIL‐53, MIL‐100, MIL‐101, UiO‐66, ZIF‐67, and ZIF‐8 will be discussed for removing various pollutants. The adsorption efficiency of functionalized MOFs, magnetic MOFs, MOF‐polymer, graphene oxide‐MOF, and CNT‐MOF composites will be reviewed in comparison with commercial adsorbents such as zeolites and activated carbon. As for the conclusion, the challenges and outlooks of applying MOFs and MOF‐based materials for the adsorptive separation of water pollutants are summarized. Abstract : In this review, the major water pollutants and their disadvantages in the aquatic environment resources have been explained. The importance of removing pollutants, mainly by applying MOFs as adsorbents, from the aquatic environment has been discussed. Possible adsorption mechanisms over MOFs, MOF production cost and MOF market are summarized. Recent findings in using different MOFs and MOF‐based adsorbents for the adsorptive separation of heavy metals, dyes, pharmaceutical, personal care products (PPCPs), pesticides, and herbicides are presented and discussed.